2020
DOI: 10.1038/s43246-020-0013-6
|View full text |Cite
|
Sign up to set email alerts
|

Rydberg excitons in Cu2O microcrystals grown on a silicon platform

Abstract: Cuprous oxide (Cu 2 O) is a semiconductor with large exciton binding energy and significant technological importance in applications such as photovoltaics and solar water splitting. It is also a superior material system for quantum optics that enabled the observation of intriguing phenomena, such as Rydberg excitons as solid-state analogue to highly-excited atomic states. Previous experiments related to excitonic properties focused on natural bulk crystals due to major difficulties in growing high-quality synt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The lack of other features in Fig. 3 (c) implies that we do not observe luminescence from the direct radiative decay of Rydberg states [47][48][49] within the sensitivity of our instrument.…”
Section: A Time-resolved Measurements and The Two-photon Emission Spe...mentioning
confidence: 82%
See 1 more Smart Citation
“…The lack of other features in Fig. 3 (c) implies that we do not observe luminescence from the direct radiative decay of Rydberg states [47][48][49] within the sensitivity of our instrument.…”
Section: A Time-resolved Measurements and The Two-photon Emission Spe...mentioning
confidence: 82%
“…We conclude that SHG spectroscopy is more sensitive to the local sample environment than absorption spectroscopy. High resolution imaging is therefore an essential tool to identify regions of good crystal quality as well as sites of potential functional microstructures [49,62,63].…”
Section: Spatially Resolved Two-photon Spectroscopymentioning
confidence: 99%
“…In fact, already a significant number of possible applications and quantum technologies based on Rydberg excitons has been proposed: It has been suggested that microcavities may help to enhance optical nonlinearities by several orders of magnitude, if the problem of phonon‐based loss channels is overcome, [ 79 ] which may pave a way towards nonlinearities on the single photon level. Also, the radiative coupling in Cu 2 O seems to be highly size‐dependent, [ 80 ] so microcrystals [ 81 ] or low‐dimensional nanostructures such as quantum dots, [ 82 ] quantum wires [ 83 ] and quantum wells [ 84 ] seem like ideal candidates for tailoring the optical properties of quantum technologies based on Cu 2 O. So far the technology for fabrication and patterning of Cu 2 O is still in its infancy, and is also challenging because the material is rather brittle.…”
Section: Discussionmentioning
confidence: 99%
“…These nonlinearities can be harnessed by quantum confinement of the excitons in semiconductor lowdimensional structures such as quantum wells and quantum * ho35@st-andrews.ac.uk dots [23]. Studying these excitons in confined dimensions is a crucial step towards harnessing these nonlinearities for applications [24,25]. Nanoparticles [26] are naturally a suitable system for quantum confinement and an interesting platform for realizing quantum technologies with Rydberg excitons, potentially underpinning future devices such as single-photon sources [27] and single-photon switches [28].…”
Section: Introductionmentioning
confidence: 99%